2016
DOI: 10.1007/s11427-016-0007-7
|View full text |Cite
|
Sign up to set email alerts
|

Cyprininae phylogeny revealed independent origins of the Tibetan Plateau endemic polyploid cyprinids and their diversifications related to the Neogene uplift of the plateau

Abstract: Origin and diversification of the Tibetan polyploid cyprinids (schizothoracins) may help us to explore relationships between diversification of the cyprinids and the Tibetan Plateau uplift. Cyprininae phylogeny was analyzed using mitochondrial and nuclear DNA sequences to trace origins of polyploidy and diversifications of schizothoracins. Ancestral states reconstruction for ploidy levels indicated that the Cyprininae was diploid origin and the schizothoracin clades tetraploid origins. There were two diversifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 83 publications
5
50
0
Order By: Relevance
“…As the first attempt to characterize the phylogenetic relationships and divergence times of Schizothoracines on the basis of transcriptomic data, our results indicated that the common ancestor of the four Schizothoracines lived at the early part of the Oligocene (32.7 MYA), when the QTP was in the first phase of uplift (Favre et al 2015; Li and Fang 1999). The common ancestor of the two primitive Schizothoracines, S. prenanti and S. gongshanensis (which belong to the genus Schizothorax ), was estimated to be ∼5.2 MYA, which has been previously estimated to be in the Late Miocene (∼10 MYA) (He et al 2004; Wang et al 2016). Our results suggested that the common ancestor of P. kaznakovi and G. dobula diverged ∼8.1 MYA, when the QTP was in the second phase of uplift.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the first attempt to characterize the phylogenetic relationships and divergence times of Schizothoracines on the basis of transcriptomic data, our results indicated that the common ancestor of the four Schizothoracines lived at the early part of the Oligocene (32.7 MYA), when the QTP was in the first phase of uplift (Favre et al 2015; Li and Fang 1999). The common ancestor of the two primitive Schizothoracines, S. prenanti and S. gongshanensis (which belong to the genus Schizothorax ), was estimated to be ∼5.2 MYA, which has been previously estimated to be in the Late Miocene (∼10 MYA) (He et al 2004; Wang et al 2016). Our results suggested that the common ancestor of P. kaznakovi and G. dobula diverged ∼8.1 MYA, when the QTP was in the second phase of uplift.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the common ancestor of the schizothroacine subfamily was estimated to live at the end of the Late Cretaceous (68.2 MYA) by Y. Li et al (2013), or at the Oligocene-Miocene boundary (∼23 MYA) or older by Ruber et al (2007) and Wang et al (2016). As the first attempt to characterize the phylogenetic relationships and divergence times of Schizothoracines on the basis of transcriptomic data, our results indicated that the common ancestor of the four Schizothoracines lived at the early part of the Oligocene (32.7 MYA), when the QTP was in the first phase of uplift (Favre et al 2015; Li and Fang 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive uplift of the Himalayas and subsequent uplift of the Southeastern Tibet and Yunnan Plateau (Figure S2) during the early Miocene to Pliocene (Cao et al, ; Favre et al, ; Harrison, Copeland, Kidd, & Yin, ; Ruddiman, ; Shi et al, ) would have completely divided the Bellamya lineage in the Pearl River basin from that in India and Thailand. Many studies have associated the divergence of organisms, such as in lizards, birds, frogs and fish, with the Miocene uplift of the QTP and simultaneous climate changes (Che et al, ; Guo & Wang, ; Johansson et al, ; Wang, Gan, Li, Chen, & He, ). Furthermore, the divergence between the India lineage and Thailand lineage approximately 13.03 mya (15.02 ~ 11.55 mya), coinciding with the Himalayan and Indo‐Burma Mountains (Figure S2), rapidly uplifted during the early to middle Miocene (Alam, Alam, Curray, Chowdhury, & Gani, ; Khin, Sakai, & Zaw, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…bichirs, sturgeons, paddlefishes, gars and bowfin) [2, 3]. Furthermore, additional whole-genome duplications (WGDs) took place independently in several other teleostean lineages, such as, e.g., Catostomidae [4], Cobitidae [5], Callichthyidae [6, 7], Salmoniformes [8] and especially Cyprinidae [911]. …”
Section: Introductionmentioning
confidence: 99%